Dampak NWC, GO, CAPEX, dan CCC Terhadap Nilai Perusahaan Dengan Cash Holding Sebagai Variabel Intervening - Belinda Lovely Luckyanti; Saiful Anwar (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The achievement of this study is to measure the relationship between net working capital, growth opportunity, capital expenditure, and cash conversion cycle on firm value with cash holding as an intervening variable. The population is Food and Beverage companies listed on the Indonesia Stock Exchange during the 2016-2020 period. Purposive Sampling is a technique used for sample collection by producing 19 sample companies. To solve the problem in this research, the data analysis technique applied is Partial Least Square in the form of WrapPLS software version 7.0. The results in this study are Net Working Capital, Capital Expenditure, and Cash Holding have no relationship to firm value. However, Growth Opportunity and Cash Conversion Cycle have a positive relationship to firm value. Net Working Capital has a positive relationship with cash holding. Meanwhile, Growth Opportunity, Capital Expenditure, and Cash Conversion Cycle have no relationship to cash holding. So that Cash Holding cannot mediate the relationship between Net Working Capital, Growth Opportunity, Capital Expenditure, and Cash Conversion Cycle on firm value. Keywords : Net Working Capital, Growth Opportunity, Capital Expenditure, Cash Conversion Cycle, Cash Holdings,Firm Value.